Prevalence and risk predictors of onychomycosis in patients on hemodialysis: an observation, prospective, and unicenter study in Brazil - Bersano, Jeanne Marie Queiroz Borges; Cordeiro, Matheus Gobbo; Marson, Fernando Augusto Lima (Frontiers in Medicine, 2023)
Background Onychomycoses are fungal infections that can be seen in any component of the nail unit, including the matrix, bed, and plate, and are caused by dermatophyte fungi, non-dermatophyte fungi, and yeasts. This disease affects approximately 1 to 8% of the general population and occurs in approximately 19 to 51.9% of the patients on hemodialysis. The high incidence of onychomycosis in patients on hemodialysis is associated, mainly, with immunologic deficits and histological changes caused by uremia. Methods Adult patients of the São Francisco University Hospital Hemodialysis Center were included. The following characteristics were evaluated: age, sex, body mass index, comorbidity, and household location. All patients were clinically evaluated and those with suspected onychomycosis had subungual debris of the affected nail plate collected for the direct mycological examination and fungal culture. The onychomycosis severity for those patients with a positive result in the fungal culture examination was evaluated using the Onychomycosis Severity Index system. Results The study included 151 patients, and 70 out of the 151 patients (46.4%) showed nail alteration, and among them, 31 out of the 70 patients (44.3%) had the onychomycosis diagnosis confirmed by direct mycological examination. The pathogens observed in the patients were Trichophyton rubrum [8 out of 31 (25.8%)], Trichophyton mentagrophytes [7 out of 31 (22.6%)], Scytalidium spp. [6 out of 31 (19.4%)], Candida spp. [2 out of 31 (6.45%)], Rhodotorula spp. [1 out of 31 (3.2%)], Candida albicans [1/31 (3.2%)], Penicillium marneffei [1 out of 31 (3.22%)], and T. rubrum and Rhodotorula spp. [1 out of 31 (3.2%)]. Three participants presented negative results in the culture examination, and one did not allow the collection of material for the examination. The nail involvement severity score for the majority of them was severe [23 out of 27 (85.2%)], and only 1 out of the 27 (3.7%) and 3 out of the 27 (1.1%) patients presented moderate and mild scores, respectively. The distal subungual onychomycosis occurred in 12 out of 27 (44.4%) patients, a mixed pattern occurred in 14 out of 27 (51.9%) patients, and, white superficial occurred in only 1 out of 27 (3.7%) patients. In the bivariate analysis, a higher risk of onychomycosis was associated with the male sex [23/31 (74.2%) vs. 56/120 (46.7%); OR = 3.286 (95%CI = 1.362 to 7.928)] and obesity [8/31 (25.8%) vs. 12/120 (10.0%); OR = 3.130 (95%CI = 1.150 to 8.521)]. Patients with diabetes mellitus were more susceptible to onychomycosis attacks (p-value = 0.049; 16 out of 31 (51.6%) vs. 40 out of 120 (33.3%); however, OR was 2.133 (95%CI = 0.959 to 4.648). The patients with onychomycosis were older but without a significant difference between the groups (p-value = 0.073; 66 years old vs. 58 years old). The multivariable model using the logistic regression (backward model) confirmed our results and was able to predict (81.5%) the onychomycosis-positive diagnosis (chi-square = 27.73; p-value <0.001). The age [OR = 1.036; 95%CI = 1.004 to 1.069], male sex [OR = 5.746; 95%CI = 2.057 to 16.046], and presence of obesity [OR = 4.800; 95%CI = 1.435 to 16.055] were positive and significant in predicting the onychomycosis-positive diagnosis. Conclusion In our study, onychomycosis in patients on hemodialysis was associated with a great variety of microorganisms, mainly Trichophyton species. The nail involvement severity score for the majority of patients was severe, and distal subungual onychomycosis and mixed pattern onychomycosis were the most prevalent clinical types. The main risk factors associated with onychomycosis were male sex, older age, and the presence of obesity.